Indonesia's Economic Capacity in Building Community Welfare Supported by International Economic Credibility - Nurbaiti Sakinah; Muhibban (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
This study examines the role of international economic credibility in supporting Indonesia's economic growth and the development of social welfare that is called for by international economic credibility. This study uses the concept of monitored economic growth, which ensures social welfare through the full use of increasingly efficient resources, profitable access to resources, and increasing economic development. This analysis is based on the principle of sustainable development, which emphasizes the need for economic growth to be synchronized with environmental protection and the distribution of welfare. The study also takes into account the challenges faced by Indonesia in achieving sustainable economic growth, such as the need for effective environmental policies and the promotion of inclusive economic development. The results of this study indicate that Indonesia's economic growth can be supported by international economic cooperation and the establishment of strong international economic credibility. The conclusion of the study is that Indonesia's economic growth can be strengthened through international economic cooperation and the establishment of strong international economic credibility.